Root coverage with platelet-rich fibrin in miller's class I, III, and IV gingival retractions - David A Gutiérrez; Juan Pablo Hinojosa; Juan P Pava; Ana Isabel Restrepo Dorado (Wolters Kluwer Medknow Publications, 2019)
Coronally advanced flap (CAF) with connective tissue graft (CTG) is considered as the most predictable method to treat Miller's Class I and II gingival recessions (GR). However, due to the patient's postsurgical discomfort, the difficulty of finding a donor with an adequate tissue thickness, the high costs of acellular dermal substitute among others, the platelet concentrates have been found to scaffold alternative to replace CTG as a part of the CAF treatment for GR. Nevertheless, according to the recent literature, the evidence of success in Class III and IV has been limited for CAF and platelet-rich fibrin (PRF). The purpose of this report is to present a case of multiple Miller's Class III and IV GR treated with CAF and PRF where the potential of PRF to increase gingival thickness and clinical attachment level, and improve soft-tissue healing and clinical appearance was corroborated.